Velvet Ants, Mutillidae (Insecta: Hymenoptera) - Jeffrey C. Hertz (EDIS)
EENY-378, an 11-page illustrated fact sheet by Jeffrey C. Hertz, is part of the Featured Creatures collection. It describes these members of the wasp family that are often referred to as "hairy ants", their distribution, biology, identification, Florida species and pest status. Includes keys to Florida genera and selected references. Published by the UF Department of Entomology and Nematology, March 2007.